PENDIDIKAN POLITIK PADA PEMILIH PEMULA DI MADRASAH ALIYAH MUHAMMADIYAH 1 MALANG - Romadhoan, Ach Apriyanto; Prinanda, Devita; Pradana, Hafid Adim (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
Abstract: Malang has potential beginner voters. Local government targeted to increase the participation of beginner voters for 2019’s election. The lack of awareness as a voters is the main problem for Indonesian youth especially in Malang. Political issues that could be reached from social media and internet, have a low accuracy level. Media creates the wrong information. Therefore, this program was implemented to provide political education for beginner voters in MA Muhammadiyah Malang. MA Muhammadiyah 1 Malang concerned to Indonesian political and history knowledge. However, poliitcal knowledge in MA Muhammadiyah 1 Malang still require a comprehensive socialization. The purpose of this program are creating characters and insight for the youth in election day. The output of this program is creating a beginner voters that able to be a Traning of Trainer (ToT) about political education for others students. Second, this program produces guidebook on political education for beginner voters.